PEMBERDAYAAN ANAK JALANAN MELALUI PROGRAM PELATIHAN KETERAMPILAN DAUR ULANG OLEH YAYASAN KUMALA TANJUNG PRIOK - Aura Syifa’unnisa; Isna Rahmawati (Indonesian Journal of Conservation, 2023)
Poverty is a problem that cannot be ignored. North Jakarta has become the city with the highest poverty rate in Jakarta Province for the last 2 consecutive years. The impact of poverty which is quite common in North Jakarta, namely children with poor economic and environmental conditions so that these children choose to become street children to earn a living by begging on the streets to fulfill their daily needs. The Kumala Foundation is one of the social institutions that empowers street children to develop themselves by developing soft skills such as recycling skills training for street children which aims to provide street children with skills in improving the economy. The research approach is carried out using the empowerment theory of Mardikanto and Soebianto by outlining aware-ness, capacity building and empowerment that has succeeded in providing a significant impact on street children in the results of human development, business development, environmental development and institutional devel-opment. The methodology in this study uses a qualitative descriptive method. Data collection techniques carried out by researchers using interviews, observation and documentation.